1980
DOI: 10.1007/bf02414734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity and cadmium interaction on reproduction and growth during three successive generations ofOphryotrocha labronica (polychaeta)

Abstract: The long-term effects of different cadmium (0.2 and 0.4 ppm} and salinity levels (30, 25, and 20 %0 S} on growth and egg-mass production of Ophryotrocha labronica (La Greca & Bacci} were investigated over three generations. Low salinity levels and the presence of cadmium resulted in reduced growth rates, prolonged times to reach sexual maturity, and reduced size at maturity. Three-way analysis of variance showed significant interaction effects of generation and cadmium for the different growth processes tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Capitella capitata 96 7.5 for adults; 0.22 for trochophore larvae Reish et al, 1976 Capitella capitata 96 0.6-1 Reish et al 1983 Neanthes arenaceodentata 96 12 for adults; 12.5 for juveniles Reish et al, 1976 Neanthes vaali 168 6.4 Ahsanullah, 1976Nereis virens 24,48,96 25, 25, 11 Eisler, 1971 Nereis virens 24,96,168 56, 9.3, 0.7 Eisler and Hennekey 1977 Laeonereis acuta 96 8.2349 Carricavur et al, 2018 Perinereis aibuhitensis 96 0.7934-13.5673 Wang et al, 2008 Ophrgotrocha labronica 48 4 Røed, 1980 The results of the present study in agreement with Reish et al (1976), Eisler and Hennekey (1977), Wang et al (2008) and Carricavur et al (2018) who found similar LC 50 values for 96-hr for the polychaetes C. capitata, Nereis virens, Perinereis aibuhitensis and Laeonereis acuta. In the present study 24 and 48-hrs LC 50 values were also similar to Nereis virens (Eisler, 1971).…”
Section: Species Time (Hr) Cd-lc 50 (Ppm) Referencesmentioning
confidence: 99%
“…Capitella capitata 96 7.5 for adults; 0.22 for trochophore larvae Reish et al, 1976 Capitella capitata 96 0.6-1 Reish et al 1983 Neanthes arenaceodentata 96 12 for adults; 12.5 for juveniles Reish et al, 1976 Neanthes vaali 168 6.4 Ahsanullah, 1976Nereis virens 24,48,96 25, 25, 11 Eisler, 1971 Nereis virens 24,96,168 56, 9.3, 0.7 Eisler and Hennekey 1977 Laeonereis acuta 96 8.2349 Carricavur et al, 2018 Perinereis aibuhitensis 96 0.7934-13.5673 Wang et al, 2008 Ophrgotrocha labronica 48 4 Røed, 1980 The results of the present study in agreement with Reish et al (1976), Eisler and Hennekey (1977), Wang et al (2008) and Carricavur et al (2018) who found similar LC 50 values for 96-hr for the polychaetes C. capitata, Nereis virens, Perinereis aibuhitensis and Laeonereis acuta. In the present study 24 and 48-hrs LC 50 values were also similar to Nereis virens (Eisler, 1971).…”
Section: Species Time (Hr) Cd-lc 50 (Ppm) Referencesmentioning
confidence: 99%